2005
DOI: 10.1097/01.ijg.0000145812.39224.0a
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases and Their Tissue Inhibitors in Aqueous Humor of Patients With Primary Open-Angle Glaucoma, Exfoliation Syndrome, and Exfoliation Glaucoma

Abstract: TIMP-2 is elevated in glaucomatous process over MMP-2, which support and further extend the conjuncture that the ECM accumulation rather than degradation predominates in the pathogenesis of POAG and EXG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(34 citation statements)
references
References 31 publications
1
32
1
Order By: Relevance
“…A significantly altered level of MMPs and their inhibitors in the aqueous humor obtained from POAG patients has been reported [13,15]. Ronkko et al (2007) have shown an elevated level of MMPs in the chamber angle of patients with primary open angle glaucoma in comparison to normal eyes by immunohistochemical staining [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significantly altered level of MMPs and their inhibitors in the aqueous humor obtained from POAG patients has been reported [13,15]. Ronkko et al (2007) have shown an elevated level of MMPs in the chamber angle of patients with primary open angle glaucoma in comparison to normal eyes by immunohistochemical staining [22].…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, MMPs are responsible for regulating aqueous humor from the anterior chamber of the eye and therefore have a significant impact on intraocular pressure [13,14]. A significantly altered level of MMPs in the aqueous humor of patients with diagnosed POAG has been previously described [13,15]. …”
Section: Introductionmentioning
confidence: 99%
“…In glaucoma, pathological changes occur in the trabecular meshwork and the juxtacanalicular tissue of the chamber angle. Aqueous humor (AH) drainage is influenced by the ECM, which modulates AH outflow from the anterior chamber via the irido-corneal drainage angle to regulate IOP [6]. A recent study in animal models reported that the abnormal expression of MMPs in the AH of patients with glaucoma may influence the regulation of IOP [7].…”
Section: Introductionmentioning
confidence: 99%
“…Babizhayev and Brodskaya [13] suggested that MMP-9 was related to ECM accumulation and structural ECM changes in the TM, which changed the resistance to TM and IOP in POAG patients. A significantly increased level of MMPs (including MMP-9) in the aqueous humor of patients with POAG has been reported previously [32]. …”
Section: Discussionmentioning
confidence: 92%